Comparative analysis of phytochemicals and antioxidant activities in seeds and sprouts of different varieties of radish (Raphanus sativus L.): TOPSIS-entropy weight method - Guo, Caihui; Zhu, Yi (Frontiers in Plant Science, 2025)
Many bioactive components in plants are beneficial to health, and their contents in seeds and sprouts are much higher than those in mature parts. This study intended to uncover alterations in nutritional compositions of radish seeds following germination. It also aimed to evaluate the health-promoting potential of both radish (Raphanus sativus L.) seeds and sprouts by quantifying representative bioactive compounds and antioxidants across six varieties. The ultimate goal was to identify the optimal radish variety with these beneficial properties through the TOPSIS-entropy weight method. This study measured chlorophyll, carotenoids, anthocyanins, glucosinolates (GLSs), total phenol (TP), vitamin C content, and antioxidant capacities (POD: Peroxidase; PAL: Phenylalanine ammonia lyase; T-AOC: Total antioxidant capacity) in seeds and sprouts of radish grew for 7 days. The GLSs content in seeds was 3 to 6-fold higher than that in sprouts; while contents of anthocyanin, sugar, and TP were much higher in radish seeds than those in sprouts. Chlorophyll, carotenoid content, and POD activity were significantly higher in sprouts than in seeds. Combined with the ideal solution similarity ranking preference method (TOPSIS) entropy weight method, M (Man Tang Hong) was the optimal radish variety. Sprouts generally outperformed seeds in terms of overall phytochemical composition and antioxidant capacities, except for M. Therefore, more sprouts are recommended to be consumed in daily life without choosing specific radish variety. In conclusion, this study supports the health-promoting properties of radish based on a comprehensive deciphering of the nutritional profile of radish seeds and sprouts, both of which are good sources of bioactive compounds.